Redesigning Medical Devices with Design for Manufacturing and Assembly (DFMA): Redesain Alat Terapi Kesehatan dengan Design for Manufacturing and Assembly (DFMA) - Andrew, Andrew; Karningsih, Putu Dana; Dewi, Dyah Santhi; Batan, I Made Londen; Wahjudi, Arif (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Product development in medical devices requires careful consideration of manufacturing and assembly to control cost, complexity, and safety. Specific Background An integrated cervical and lumbar traction device prototype exhibited excessive components and fasteners, resulting in low assembly efficiency, high manufacturing cost, and the absence of an emergency button. Knowledge Gap Previous traction device designs had not been systematically evaluated using Design for Manufacturing and Assembly (DFMA) with explicit assessment against Design for Assembly guidelines. Aims This study aims to redesign the integrated cervical and lumbar traction device using DFMA to reduce manufacturing cost and assembly time while incorporating an emergency button. Results The redesign achieved a 77.06% reduction in reorientation operations and a 53.19% decrease in insertion difficulties, leading to a 16.90% increase in assembly efficiency, an 11.07% reduction in total assembly time, and a 9.12% decrease in manufacturing cost. The DFA Index increased from 7.1 to 8.3, indicating improved assembly performance. Novelty The novelty lies in evaluating redesign outcomes through systematic compliance with DFA Guidelines supported by Boothroyd Dewhurst DFMA software. Implications The findings demonstrate that DFMA provides a structured approach for developing medical therapy devices that are easier to assemble, more cost-efficient, and safer for users, offering a practical reference for similar healthcare equipment redesign initiatives. Highlights: Structural simplification and fastener standardization substantially reduced assembly complexity. Quantitative DFA metrics confirmed notable reductions in reorientation and insertion difficulties. Manufacturing and assembly costs per unit decreased while safety functionality was incorporated. Keywords: Assembly Efficiency, DFMA, Manufacturing Cost, Medical Therapy Device Redesign